A Comparative Analysis of Lauren Wellbank’s ”The Boy and The Tree” and Steven Moe’s “The Apple Tree”: Ecocriticism Approach - Nanyan, Tiffani Willin (Proceedings of English Linguistics and Literature, 2024)
Humans have a very important role in maintaining the balance of the earth's ecosystem. Human actions that are not wise in maintaining and caring for nature have resulted in damaging the ecosystem and giving impacts such as natural disasters that occur in Indonesia and abroad these days. Lauren Wellbank’s ”The Boy and The Tree” and Steven Moe’s “The Apple Tree” highlight the connection between humans and trees, emphasizing human influence on nature and the significance of protecting and maintaining the natural environment. This paper aims to analyze the human-nature interactions and the impact of human actions depicted in the two stories. This research shows that the consequences of overexploitation of natural resources have resulted in many adverse impacts on the climate, wildlife habitats and wider environmental damage. The environmental damage that continues today puts the health of our planet at risk. Thus, the personification of trees, depicted as a living being that can speak and feel, leaves a message to remind humans of their ecological responsibilities to protect and preserve nature.